2022
DOI: 10.3390/nu14081601
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Nutritional Support: A Review of Current Literature

Abstract: Since the beginning of the practice of surgery, the reduction of postoperative complications and early recovery have been two of the fundamental pillars that have driven the improvement of surgical techniques and perioperative management. Despite great advances in these fields, the rationalization of antibiotic prophylaxis, and other important innovations, postoperative recovery (especially in elderly patients, oncological pathology or digestive or head and neck surgery) is tortuous. This can be explained by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 164 publications
1
42
1
2
Order By: Relevance
“…Although we found lower serum albumin levels in patients with lower preoperative PhA, the preoperative PhA was not influenced by the preoperative serum albumin levels in our cohort. Nevertheless, our observed serum albumin levels were higher than reported levels associated with cardiac cachexia or increased mortality, even in the cohort with low PhA [37].…”
Section: Discussioncontrasting
confidence: 87%
“…Although we found lower serum albumin levels in patients with lower preoperative PhA, the preoperative PhA was not influenced by the preoperative serum albumin levels in our cohort. Nevertheless, our observed serum albumin levels were higher than reported levels associated with cardiac cachexia or increased mortality, even in the cohort with low PhA [37].…”
Section: Discussioncontrasting
confidence: 87%
“…Despite great advances in surgical techniques, postoperative recovery of cancer patients is tortuous, where malnutrition plays a major role ( 32 ). Our nationwide data analysis revealed that patients with PEM had a 2.26-fold risk of mortality compared to those without PEM after MCS, which was consistent with previous studies focusing on one specific cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with patients without sarcopenia, the short-term quality of life after laparoscopic surgery was significantly improved in those with sarcopenia. Nutritional status is one of the most recognized determinants of surgical outcomes and is associated with poor postoperative outcomes [ 45 ]. Approximately 40% to 50% of patients undergoing surgery have some degree of malnutrition [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a treatment, HCC induces inflammatory responses and related neurohumoral regulation, leading to the upregulation of inflammatory cytokines such as interleukin (IL)-1, IL-2, and IL-6. Simultaneously, the levels of anti-inflammatory cytokines such as IL-4 and IL-10 are also increased to induce a stress response [ 45 ]. The activation of both the inflammatory and anti-inflammatory responses negatively impacts metabolism, bone density, muscle mass and strength, exercise tolerance, the circulation system, cognition, and emotion, all of which significantly increase surgical risk and worsen outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation